Endoparasites in the annual cycle of feral Greylag Geese Anser anser - Woog, Friederike; Maierhofer, Jana; Haag, Holger (Wildfowl, 2013)
The monthly occurrence of endoparasites in feral Greylag Geese Anser anser near Stuttgart, southwest Germany was studied in 2007 and 2008. Seven genera of parasites were found in the faecal samples. Nematode ova were most prevalent, followed by protozoan oocysts, whereas only a few cestode ova were recovered. The level of parasite infestation varied regionally and seasonally. More birds were found to have parasites in winter than in summer, which was reflected by a negative correlation between mean monthly temperature and the percentage of geese with parasites. Parasite loads were low and there was no measurable negative effect of parasites on the body condition of the geese.